2015
DOI: 10.1007/s00259-015-3190-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of PRRT in advanced bronchopulmonary carcinoid

Abstract: In a large cohort of patients with advanced BPC treated in a "real-world" scenario and followed up for a median of 45.1 months (range 2-191 months), PRRT proved to be promising in prolonging survival and delaying disease progression. Despite the potential selection biases, considering the risk-benefit ratio, (177)Lu-DOTATATE monotherapy seems the best option for PRRT. Our results indicate that the use of PRRT in earlier stages of the disease could provide a more favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 23 publications
6
78
1
Order By: Relevance
“…Our data showed a reduction in PFS and OS in both univariate and multivariate analysis in patients pretreated with chemotherapy, as was also demonstrated in other studies (23,25). Additional analysis in our dataset revealed that of the 43 patients with a G3 tumor, 19 (44%) were treated with chemotherapy, whereas among patients with G1 and G2 tumors, only 12% and 23%, respectively, were treated with chemotherapy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data showed a reduction in PFS and OS in both univariate and multivariate analysis in patients pretreated with chemotherapy, as was also demonstrated in other studies (23,25). Additional analysis in our dataset revealed that of the 43 patients with a G3 tumor, 19 (44%) were treated with chemotherapy, whereas among patients with G1 and G2 tumors, only 12% and 23%, respectively, were treated with chemotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…The reported PFS in other studies (32-41 mo) is higher than in the current study (22 mo). Meanwhile, the OS (43 mo) of the current patient cohort was within the reported range in the literature (38-82 mo) (21)(22)(23)(24)(25)(26). However, differences between the current study and the literature exist.…”
Section: Discussionsupporting
confidence: 61%
“…Studies of therapies in the advanced or metastatic lung carcinoid setting have been limited to retrospective analyses and some small prospective studies (6,(38)(39)(40). Recent articles reviewed the current standard of care and recent advances in therapy for bpNETs (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Non-controlled studies in PanNEN and SBNEN have demonstrated its effectiveness: objective responses ( Fig. 6, 7) occur in 28-39% [227,228], symptomatic improvements have been noted and a positive impact on survival parameters is documented [152,228,229]. A recent phase III, randomised, controlled trial of midgut NEN, progressive on standard-dose octreotide LAR (NETTER-1), demonstrated 177 Lu-DOTATATE to be more effective than high-dose octreotide LAR (median PFS 28.4 vs. 8.4 months), resulting in a 79% reduction of the risk of progression and a significant symptomatic improvement (e.g., fatigue, diarrhoea, pain) [9,230].…”
Section: Peptide Receptor Radionuclide Therapymentioning
confidence: 99%